Different fractions from wheat flour provide distinctive phenolic profiles and different bioaccessibility of polyphenols following in vitro digestion. (15th March 2023) - Zhang, Leilei; García-Pérez, Pascual; Martinelli, Erika; Giuberti, Gianluca; Trevisan, Marco; Lucini, Luigi
Highlights: Wheat flours and by-products were subjected to untargeted phenolic profiling. Ferulic acid, lignans and alkylresorcinols were found as cell wall-bound phenolics. Flavonoids, especially anthocyanins, were predominantly found as free phenolics. An in vitro digestion model was performed to assess the phenolic bioaccessibility. Lignans from wholegrain flours were reported as the major bioaccessible compounds. Abstract: Wheat is a prevalent food worldwide, although its production arises several tonnes of industrial by-products that merit valorisation, owing to sustainable demands. In this work, an untargeted metabolomics approach was applied to shed light on the profile of free and bound phenolic compounds in white and wholegrain flours, as well as the major wheat by-products, namely wheat bran, wheat shorts and wheat middlings. By-products and wholegrain flours were found to be rich sources of ferulic acid derivatives, lignans, and alkylresorcinols, mostly bound to wheat fibre components, whereas different flavonoids were found in their free forms. Afterwards, the in vitro gastrointestinal digestion of these matrices showed that flour phenolics, in particular lignans, were more bioaccessible than those from wheat by-products. These results support the carrier effect attributed to dietary fibre and open a wide perspective on the use of underexploited wheat by-products to formulate novel functional foods.